SALAT BERKUALITAS SALAT BERJIWA IHSAN - Slamet Firdaus (IAIN Syekh Nurjati Cirebon, 2015)
Ibadah yang intinya adalah dzikir kepada Allah swt dipastikan berdampak positif bagi para pelakunya, terutama ibadah yang berdimensi dialog antara hamba dan Dhat yang wajib disembah semacam salat. Salat yang disyariatkan-Nya dapat mencegah perbuatan keji dan munkar. Pencapaiannya tidak serta merta melalui pengamalan salat semata, melainkan ditopang sepenuhnya oleh kualitas pengamalan yang memadai, yakni salat yang ditegakan dengan berjama’ah, pada awal waktu, dan dijiwai ihsan. Potret pribadi yang sukses memperolehnya merupakan model insan berkarakter dan memiliki nilai kehidupan yang berhasil mengharmonikan antara komponen lahiriah salat (syarat dan rukun) dan ruhnya (khusyu dan ikhlas) yang kemudian terejawantahkan dalam tatanan kehidupan individual dan kolegial.Worship, the essence of which is the dhikr to Allah, certainly has a positive impact upon the worshipers. This is true especially for the worship which has dialogical dimension between the servant and God who must be worshiped as in Salat. Salat which He has mandated will prevent indecency and evil. Its achievement is not necessarily through the practice of prayer alone, but fully supported by the practice of adequate quality of performance, which is upheld by the prayers in congregation, at the beginning of time, and imbued by ihsan. A personal portrait, who could successfully obtain it, is a model of human character that has integrity and the value of life that successfully harmonize between external components of Salat (by fulfilling its conditions and pillars), and its spirit (humility and sincerity) which is then realized in the order of individual and collegial life.